(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
Prader-Willi syndrome (PWS) is a genetic disorder caused by a deletion of genes in region 15q11-13. It is associated with intellectual disability and unwieldy neurobehavioral alterations. The aim of the study was to compare behavior problems of two groups of children and adolescents with PWS considering the possibility of free or restricted access to food at home. The sample was composed of 12 children and adolescents with cytogenetic-molecular diagnosis of SPW (6 in each group) and their mothers. Children and adolescents had their body weight recorded and the Child Behavior Checklist for ages 6-18 years old (CBCL/6-18) was answered by the mothers. The groups presented statistically significant differences related to problems of anxiety and depression, violation of rules and defiance and opposition. The group with restricted access to food presented more behavioral problems.